Production of plasmid-encoding NDM-1 in clinical Raoultella ornithinolytica and Leclercia adecarboxylata from China - Sun, Fengjun; Yin, Zhe; Feng, Jiao; Qiu, Yefeng; Zhang, Defu; Luo, Wenbo; Yang, Huiying; Yang, Wenhui; Wang, Jie; Chen, Weijun; Xia, Peiyuan; Zhou, Dongsheng (Frontiers in Microbiology, 2015)
Raoultella ornithinolytica YNKP001 and Leclercia adecarboxylata P10164, harboring conjugative plasmids pYNKP001-NDM and pP10164-NDM with determination of complete nucleotide sequences, respectively, were isolated from two different Chinese patients. Production of NDM-1 enzyme by these plasmids accounts for carbapenem resistance of these two strains. This is the first report of blaNDM in L. adecarboxylata and the third report of this gene in R. ornithinolytica. pYNKP001-NDM is very similar to the IncN2 NDM-1-encoding plasmids pTR3, pNDM-ECS01 and p271A, while pP10164-NDM is similar to the IncFIIY blaNDM-1-carrying plasmid pKOX_NDM1. The blaNDM-1 genes of pYNKP001-NDM and pP10164-NDM are embedded in Tn125-like elements, which represent two distinct truncated versions of the prototype NDM-1-encoding Tn125 as observed in pNDM-BJ01. Flanking of these two Tn125-like elements by miniature inverted repeat element (MITE) or its remnant denotes MITE felicitates transposition and mobilization of blaNDM-1 gene contexts.